Intestinal Continuity Alleviates Pediatric Intestinal Failure-Associated Liver Disease - Wang, Jinling; Yan, Weihui; Lu, Lina; Tao, Yijing; Huang, Liufang; Cai, Wei; Wang, Ying (Frontiers in Surgery, 2022)
Background Type I short bowel syndrome (SBS) occurs after a critical reduction in the functional gut mass and resection of intestinal continuity after ileostomy or jejunostomy for necrotizing enterocolitis (NEC), intestinal atresia or other causes. SBS is often accompanied with intestinal failure-associated liver disease (IFALD) who requires long-term parenteral nutrition (PN). Our study aimed to observe the effect of intestinal continuity on the hepatic function of pediatric intestinal failure (IF) patients with type I SBS. Methods The pre-and post-anastomosis medical records of 35 pediatric patients with type I SBS from April 2013 to April 2019 were reviewed retrospectively. The average growth (cm/month) in the proximal and distal small bowel lengths was calculated as the growth in intestinal length (cm)/the duration (month) from enterostomy to anastomosis. The changes in hepatic function from enterostomy to anastomosis were evaluated by assessment of hepatic function before anastomosis for 6 weeks and after anastomosis for 4 weeks. Results The average growth in proximal intestinal length was 9.3 cm/month (±7.2) in neonates and 2.8 cm/month (1.3, 11.9) in infants and children, and in distal intestinal length was 1.5 cm/month (0, 2.7) in neonates and 0.4 cm/month (0, 1.4) in infants and children. The incidence of IFALD was 28.6% 1 month before anastomosis and 20.0% 1 month after anastomosis (p < 0.05). Conclusion In pediatric type I SBS with IFALD, restoration of intestinal continuity may alleviate liver injury. There was an intestinal compensatory effect on the growth in the intestinal length after resection, and better results were seen in neonates in terms of intestinal length growth.